The Farming Land Tenure by Corporation: People’s Economic Rights Protection Perspective - Multifiah, Multifiah; Ekawaty, Marlina; Herdiastiti, Debby Radina (International Journal of Social and Local Economic Governance, 2015)
Recruitment is a series of events to find and attract job applicants motivation, ability, skills and knowledge required in order to cover the flaws identified in the staffing plan. In most of the industrial age, family networks continue to complement the main base manpower recruitment. The purpose of this study is to determine the role of social capital networks as a method of recruitment. The analysis method used is descriptive qualitative approach. "Contacts " in the network to help job seekers with a very effective way to find new jobs. Social capital is measured by the extent of the network - a network of friends. Bridging social capital a person enters the labor market as well as those who are still unemployed . Salt cellar is one of the cigarette industry that leverage social capital networks in recruitment method. In addition to family networks, private networks in each individual also profitable. On the side of the ladder for example. Size of personal networks of individuals have a positive influence and should be counted on the possibility of getting a job. Private network through friends, neighbors and contacts also help candidates salt warehouse laborers to enter the enterprise. In conclusion, the significant role of social capital networks in recruitment in PT Gudang Garam Tbk Kediri, East Java. Skipped Network is friendship, family, and " contact" (personal networks).